DETERMINATION of THE FUNDAMENTAL CHARACTERISTICS of COLD STARS - Belik, S. I.; Komarov, N. S.; Dragunova, A. V. (Одеські астрономічні публікації, 2017)
The effective temperatures, logarithms of surface gravities and parameters of metallicities [Fe/H] for stars of spectral classes G and K from the list of theOdessacatalogue of energy distributions in spectra of stars 555 are received. The different grids of Kurucz models of atmospheres are used. The comparison of the received results is carried out.